PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEJAKSAAN TINGGI MALUKU UTARA - Rasid, Saiful; Wahab Hasyim, Abdul; Abdul Haji, Sulfi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The purpose of the study was to analyze and analyze the influence of transformational leadership style on employee performance at the North Maluku High Prosecutor's Office. To find out and analyze the influence of emotional intelligence on employee performance at the North Maluku High Prosecutor's Office. To find out and analyze the influence of work stress on employee performance at the North Maluku High Prosecutor's Office. This study uses a quantitative method. The population is employees of the North Maluku High Prosecutor's Office with a sample of 87 employees. Data collection techniques using questionnaires. Data analysis using multiple linear regression analysis. Hypothesis testing using t-test, F-test, coefficient of determination. The results of the study indicate that there is an influence of transformational leadership style on employee performance at the North Maluku High Prosecutor's Office. There is an influence of emotional intelligence on employee performance at the North Maluku High Prosecutor's Office. There is an influence of work stress on the performance of employees of the North Maluku High Prosecutor's Office.